Pemanfaatan Air Hujan Dalam Perspektif Al-Qur'an: Studi terhadap Al-Qur’an Surah Al-Anfal Ayat 11 Menurut Buya Hamka - Khairullah, Muhammad Farhan; Zuhri, Ahmad; Yuzaidi (Ikatan Da'i Indonesia, 2023)
Utilization of Rainwater in the Perspective of the Koran (Study of the Koran Surah al-Anfal Verse 11 According to Buya Hamka). Rain is a form of natural balance created by Allah SWT. Without rain, the quantity of water on earth will not be sufficient for life in it.This research focuses on examining the opinion of a person that rain always causes disaster, not a blessing. Because with one of the changes in the weather that can cause disaster, it makes a person forget the favors or benefits behind something that God created, like rain. Rainwater is an abundant source of water, especially during the rainy season. Conversely, if rainwater is not managed properly, it can cause disasters, such as floods and landslides. From this background, the author raises this theme focusing on the formulation of the problem as follows. 1) Buya Hamka's interpretation of surah Al-Anfal verse 11? 2) Knowing the benefits of rain for health according to surah Al-Anfal verse 11?. This research is a library research that makes Tafsir Al-Azhar the primary source. The method in this research is to use the tahlili interpretation method. with other words in one verse or several verses. From the results of this study, the authors found that the rainwater described in the Qur'an is not just water that we usually encounter in everyday life, but also explained about rainwater that rainwater can clean oneself clean and open. Rainwater can also eliminate whispers. devil whispers. And rainwater also brings joy and freedom, the heart is strong and firm